2020
DOI: 10.1029/2019gc008787
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Dimensional Magnetic Models of La Gomera (Canary Islands): Insights Into the Early Evolution of an Ocean Island Volcano

Abstract: An aeromagnetic data set from the island of La Gomera was studied through two inverse modeling approaches that produced complementary views of the inner structure of this volcanic island: (1) a variable magnetization model that identified the main lateral magnetization contrasts and (2) a constant magnetization model that imaged the main magnetic source by assuming that it was a uniformly magnetized body. The modeling reveals intense magnetizations beneath the northern part of La Gomera, which occupy an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Potential field methods have been widely used to study volcanic islands to obtain 3D models of the inner volcanic systems to image magma intrusion beneath the surface. This allows us to delineate the main volcanic structures and constrain the locations of dense intrusive basaltic and ultramafic bodies, as well as geothermal areas, related to the heat flow along the plumbing system (e.g., [3][4][5][6][7][8][9][10]).…”
Section: Introductionmentioning
confidence: 99%
“…Potential field methods have been widely used to study volcanic islands to obtain 3D models of the inner volcanic systems to image magma intrusion beneath the surface. This allows us to delineate the main volcanic structures and constrain the locations of dense intrusive basaltic and ultramafic bodies, as well as geothermal areas, related to the heat flow along the plumbing system (e.g., [3][4][5][6][7][8][9][10]).…”
Section: Introductionmentioning
confidence: 99%
“…The NNW-SSE orientation matches the orientation of stresses obtained by [33] using data from the moderate Mw 5.0 earthquake that occurred between Tenerife and Gran Canaria in 1989 and agrees with the orientation of the regional compression model described by [36,37] for the archipelago. Recent aeromagnetic studies by [38][39][40] in the central islands of the archipelago revealed elongated anomalies with E-W (Tenerife and La Gomera) and ENE-WSW (Gran Canaria) orientations. Furthermore, [39] accounted for the intrusive body found in the submarine edifice of Gran Canaria, which has an ENE-WSW orientation that coincides with the aforementioned fracture suggested by [28].…”
Section: Geodynamic and Tectonic Contextmentioning
confidence: 99%
“…More recently, refs. [39,40] suggested that such an orientation could be responsible for the ascent and emplacement of magmas in the early formation phases of the central islands of the archipelago. Moreover, such a deformation pattern with an east-west orientation in the central islands is consistent with the existence of the major tectonic feature that connects the Trans-Alboran Fault System with the Mid-Atlantic Ridge, as suggested by [24] (see Figure 1).…”
Section: Trianglementioning
confidence: 99%
See 1 more Smart Citation